Patterns of Corruption Prisoners Development In Indonesia In Realizing The Objective of Corruption - Darmawati Darmawati; Asriadi Zainuddin (Faculty of Law, Musamus University, 2021)
Implementation of Guidance on Corruption Convicts is one of the things that must receive attention in prisons because it is one of the Extra Ordinary Crimes. In addition, most corruption crimes are committed by people who have a high social status, both in terms of their position before staying in prison as well as in terms of education and economic levels. Arrangements regarding the implementation of guidance for corruption convicts in Indonesia are regulated in the provisions of Law Number 12 of 1995 concerning Corrections and are described through Government Regulation Number 31 of 1999 concerning Guidance and Guidance of Correctional Citizens. Regarding the guidance for corruption convicts, it still refers to the provisions of Government Regulation Number 31 of 1999 where there is no difference in terms of the implementation of coaching which is still carried out through three stages, namely the initial stage, the advanced stage and the final stage. To be able to obtain the right to parole, there are special provisions that are applied to Corruption Convicts, namely in addition to having to behave well while in prison, they must also fulfill the obligation to complete the payment of fines or replacement money to be able to submit a parole proposal.